Physical Chemistry of Binary Organic Analogues of Nonmetal-Nonmetal Eutectics. - RAI, U.S.; SHEKHAR, H. (Asian Journal of Chemistry, 2010)
Phase diagram of phenanthrene with each of benzidine, o-phenylenediamine and p-phenylenediamine and β-naphthylamine, determined by the thaw-melt method, shows the formation of a eutectic in all the systems. The values of linear velocity of crystallization (v) determined at different undercoolings (ΔT) by measuring the rate of movement of solid/liquid interface in a capillary show their linear dependence in the logarithmic plots of log v vs. log ΔT. From the values of enthalpy of fusion of pure components and eutectics the values of enthalpy of mixing were calculated.